Are our orchids safe down under? A national assessment of threatened orchids in Australia - Backhouse, Gary (2015)
Australia has about 1700 species of orchids, com- prising about 1300 named species in about 190 gen- era, plus at least 400 undescribed species (Jones 2006, pers. comm.). About 1400 species (82%) are geophytes, almost all deciduous, seasonal species, while 300 species (18%) are evergreen epiphytes and/or lithophytes. At least 95% of this orchid flora is endemic to Australia. While the tropical and subtropi- cal epiphytic/lithophytic orchid flora is low by world standards, the temperate terrestrial orchid flora is amongst the richest and most diverse of any compara- ble region in the world.